Retinoblastoma: Advanced Imaging, Clinical Approach - Feygin, Tamara; Leahey, Ann-Marie (Journal of Pediatric Neuroradiology, 2015)
Retinoblastoma (RB) is a malignant tumor of the retina and the most common intraocular pediatric tumor. It typically affects children younger than 4 years of age. Loss or mutation of RB genes causes absence of RB control protein and subsequent uncontrolled cell division and tumor growth. In this review article, we describe how two forms of RB—germline (40%) and somatic sporadic (60%)—differ in their clinical presentation and prognosis. The accurate diagnosis, staging, and monitoring of the disease may be achieved with a combination of ophthalmologic examination, genetic analysis, and modern imaging. We refer to a spectrum of clinical and imaging modalities, which may be used in the diagnosis of RB. The advantages and shortcomings of ocular ultrasound, orbital computed tomography, and magnetic resonance imaging (MRI) are described. Modern imaging protocols allow for better assessment of disease extension and can help make treatment decisions for eye-sparing procedures in some cases to avoid enucleation. Essential components of optimal orbital MRI are emphasized. The roles of various MRI sequences are highlighted for demonstration of original tumor morphology and extension, and for the accurate assessment of disease progression and response of RB to treatment on follow-up examinations. Imaging features of aggressive or advanced disease and normal appearance of posttreatment eye and posttreatment complications are also illustrated.
Keywords: retinoblastoma; RB1 gene; orbital imaging; treatment-related complications